Fertigation in sprinkler irrigated upland rice (Oryza sativa L.) - Shahanila P P (Department of agronomy, College of horticulture, 2015)
Upland rice cultivation is now being promoted by the Kerala government in the context of diminishing area and production of rice. Although traditionally raised as rainfed crop in the first crop season, upland rice can also be grown throughout the year, if irrigation is provided. Micro irrigation techniques are now gaining popularity because of scarcity of water and high water use efficiency. Irrigation through micro sprinklers is advantageous for upland rice. The present study was undertaken to standardize the irrigation and nutrient requirement of high yielding rice variety grown in upland situation. The experiment was conducted at the Instructional Farm of KAU, Vellanikkara during February to June 2014. The trial was laid out in split plot design with four main plots and three subplots and replicated thrice. The treatments consisted of four levels of irrigation; irrigation @ 75% pan evaporation (Ep) (I1), 100% pan evaporation (I2), 125% pan evaporation (I3) and life saving irrigation (I4) at 5cm depth at required stages and three fertilizer levels; 90:45:45 N, P2O5, K2O kg/ha (F1), 70:35:35 N, P2O5, K2O kg/ha (F2) and 60:30:30 N, P2O5, K2O kg/ha (F3). Biometric characters such as plant height and tiller number per hill were higher in the irrigation schedule of 125% pan evaporation at all the crop growth stages. There was no significant difference among fertilizer levels with regard to plant height and tiller number at 30 DAS and at harvest. The quantity of irrigation water significantly influenced the yield and yield attributes of rice. The highest number of panicles per hill, filled grains per panicle, total biomass production, grain and straw yield were in the highest irrigation level of 125% pan evaporation. Nitrogen and phosphorus contents in rice were not altered with irrigation levels at 30 DAS. The phosphorus content showed an increasing trend with increase in irrigation level from 75% to 125% pan evaporation. At 60 DAS, the highest nitrogen content was observed in irrigation at 75% pan evaporation and the highest phosphorus content was under 125% pan evaporation. Nitrogen and phosphorus content in grains were altered by moisture regime whereas potassium content was not influenced. In straw, phosphorus and potassium contents were altered by irrigation levels and higher contents were registered in 100% pan evaporation and life saving irrigation respectively. The uptake of all the three basic nutrients showed an increasing trend with increase in irrigation level and the highest uptake was recorded under the high irrigation level of 125% pan evaporation. Only nitrogen uptake was significantly influenced by fertilizer levels and the highest uptake was registered with a fertilizer dose of 90:45:45 N, P2O5, K2O kg/ha. Field water use efficiency showed a decreasing trend with increase in irrigation level and it was higher for crop grown under 75% pan evaporation irrigation level. The results of moisture studies indicated that rice extracted more moisture from the top 30 cm soil layer. In general, weed density was high under sprinkler irrigation. Panicum maximum (Guinea grass) was the only monocot weed found in the experimental plot. Borreria hispida, Melochia corchorifolia, Centrosema pubescens, Calopogonium mucunoides, Cleome spp. were the dicot species. Density of monocots and weed dry weight was higher in 125% pan evaporation irrigation whereas density of dicot weeds were higher in 75% pan evaporation. Throughout the crop growth stages, weed density was not significantly influenced by fertilizer levels. In the present study, the highest return from sprinkler irrigated upland rice was obtained with an irrigation regime of 125% pan evaporation and fertilizer dose of 60:30:30 N, P2O5, K2O kg/ha.